ChemInform Abstract: A D‐Ribose‐Derived α‐Amino Nitrile as a Versatile Intermediate for the Collective Synthesis of Piperidine‐Type Iminosugar C‐Glycosides. Issue 17 (April 2015) - Hu, Xiang‐Guo; Daryl Ariawan, A.; Hunter, Luke
Abstract Treatment of α‐amino nitrile (I) with AgBF4 generates an iminium salt intermediate, which is readily functionalized with Grignard reagents to form C‐glycoside products with excellent stereocontrol.